2013
DOI: 10.1007/s10689-013-9674-3
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk and genotype–phenotype correlations in PTEN hamartoma tumor syndrome

Abstract: Patients with germline PTEN mutations are at high risk of developing benign and malignant tumours. We aimed to evaluate the cumulative risk of several types of cancer and of dysplastic cerebellar gangliocytoma (Lhermitte-Duclos disease, LDD). In addition, genotype-phenotype correlations in PTEN hamartoma tumour syndrome (PHTS) were assessed. Data on patients with PTEN mutations were collected from clinical genetic centres in Western Europe, Australia, and the USA. The cumulative risk of developing cancers of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 17 publications
3
90
0
9
Order By: Relevance
“…[6] The same registry reported a higher incidence of colorectal cancer among patients with PTEN frameshift mutations compared to missense or promoter mutations, while another registry reported lower rates of thyroid cancer in missense mutation patients. [7,10] The present family demonstrates clinical features consistent with these genotype-phenotype correlations, with thyroid cancer occurring in Patient II-2, and prominent colonic involvement in both affected patients. Although DNA from Parents I-1 and I-2 was not available for analysis, as they are alive and reportedly without symptoms, we speculate that the PTEN mutation arose de novo in Patient II-2.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…[6] The same registry reported a higher incidence of colorectal cancer among patients with PTEN frameshift mutations compared to missense or promoter mutations, while another registry reported lower rates of thyroid cancer in missense mutation patients. [7,10] The present family demonstrates clinical features consistent with these genotype-phenotype correlations, with thyroid cancer occurring in Patient II-2, and prominent colonic involvement in both affected patients. Although DNA from Parents I-1 and I-2 was not available for analysis, as they are alive and reportedly without symptoms, we speculate that the PTEN mutation arose de novo in Patient II-2.…”
Section: Discussionsupporting
confidence: 74%
“…[25] The autosomal-dominant and highly-penetrant PHTS conditions are characterized by a broad range of manifestations including macrocephaly, skin abnormalities, neurologic problems, and hamartomatous or ganglioneuromatous gastrointestinal polyposis. [6,7] Harmartomatous polyps of the stomach and colorectum define the related but distinct autosomal-dominant Juvenile Polyposis Syndrome (JPS), which results from germline mutations of SMAD4 or BMPR1A disrupting signaling through the bone morphogenetic protein (BMP)/SMAD4 pathway. [8,9]…”
Section: Introductionmentioning
confidence: 99%
“…There are no conclusively established genotype-cancer phenotype correlations (10). However, individuals with missense pathogenic variants in the PTEN gene may have a lower risk of thyroid cancer than other mutation types (11).…”
Section: Phtsmentioning
confidence: 99%
“…Breast and thyroid carcinoma are found more frequently in adult patients with PHTS than in the general population 3. The cumulative cancer risk for all cancers seems to be higher in women with PHTS than in men (87% vs 56%) even when excluding female-only cancers 4. Children with PHTS often manifest macrocephaly, variable degrees of developmental delay/intellectual disability, autism spectrum disorders, pigmented penile macules in males, vascular anomalies and intestinal hamartomatous polyps 5.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have suggested that patients with missense PTEN mutations may have a lower risk of thyroid carcinoma,4 those with mutations in the promoter of the gene may have a higher risk of breast cancer3 and those with non-sense PTEN mutations may be at an increased risk of colorectal cancer, although these observations have not been confirmed.…”
Section: Introductionmentioning
confidence: 99%